2008
DOI: 10.5009/gnl.2008.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Relapse of Autoimmune Pancreatitis

Abstract: Autoimmune pancreatitis (AIP) is a peculiar type of chronic pancreatitis whose pathogenesis involves autoimmune mechanisms. The steroid responsiveness has a significant impact on the diagnosis of AIP because patients with AIP and pancreatic cancer share many clinical features. This review focuses on the treatment and relapse of AIP. The goal of AIP treatment is remission of symptoms, serology, radiologic changes, or histology, which also applies to relapse. Although it is generally agreed that steroids should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Relapse was the only significant independent predictive risk factor for serious side effects in the multivariate analysis (OR 4.065; 95% CI 1.125-14.706; p = 0.032). The rate of relapse is reportedly 15%-60% [22][23][24][25]. In the present study, the incidence of AIP relapse was 23.8% (20/84), which was similar to previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Relapse was the only significant independent predictive risk factor for serious side effects in the multivariate analysis (OR 4.065; 95% CI 1.125-14.706; p = 0.032). The rate of relapse is reportedly 15%-60% [22][23][24][25]. In the present study, the incidence of AIP relapse was 23.8% (20/84), which was similar to previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The value of long-term low-dose maintenance corticosteroid therapy to avoid recurrence in autoimmune pancreatitis, a subtype of IgG4-RD, is well known 24. However, the duration of maintenance therapy has not yet been established 25. The results of our study showed the systemic maintenance of corticosteroids over 5 months could be suggested for initial treatment to reduce the risk of recurrence, and further prospective studies are needed to establish effective regimens of long-term low-dose corticosteroids to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Because AIP cases sometimes closely mimic pancreatic cancer, their responsiveness to steroid therapy is one of the important diagnostic criteria of AIP. 23 In our study, we used the AIP criteria published by Kim et al 10,13,14 As reported previously, 3 both types of AIP responded to steroid initially but only patients with LPSP developed recurrences. Interestingly, LPSP cases with recurrences exhibited extrapancreatic involvement more frequently than those without recurrences.…”
Section: Discussionmentioning
confidence: 96%